SOME PERMEABILITY PROPERTIES OF ISOLATED RAT LIVER CELL MITOCHONDRIA - Jackson, Kenneth L. (The Rockefeller University Press, 1956)
The rates of penetration of various solutes into isolated rat liver mitochondria have been studied. Sodium, potassium, and sucrose were observed to enter the mitochondria until an equilibrium concentration was reached. The diffusion of these solutes, after the first few minutes, followed the predicted diffusion curve for solutes entering a particle with a rate-limiting membrane and instantaneous mixing in the interior. Reasons for deviations from the predicted equation during the first few minutes of diffusion are suggested. The data show that at pH 7.4 sodium and potassium enter more rapidly than sucrose. I(131)-labelled albumin was found to enter very slowly, if at all. Increasing the pH from 7.4 reduced the rate at which sodium ion penetrated the mitochondria. The rate of diffusion of sucrose into mitochondria was considerably slower than diffusion of sucrose into a sphere of water of the same size. Sodium ion was not found to be concentrated in vitro against an external concentration gradient as has been reported by other investigators. It is concluded that the rate of diffusion of solutes between the external medium and the interior of mitochondria is probably restricted and controlled by a mitochondrial membrane exhibiting passive permeability characteristics.